Horse driven grain thresher in operation - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
A grain thresher powered by an eighteen horse team in operation at a unidentified location. There are crew of seven agricultural laborers working on the thresher. On the right, a part of the field that has been harvested is visible.